Skeletal characteristics and population demography as reflected by materials from Toutswe tradition sites in eastern Botswana, west of the Shashe-Limpopo basin - Steyn, Maryna (University of Pretoria, 2013)
Dissertation (MSc (Anatomy))--University of Pretoria, 2007.